2021
DOI: 10.21831/jpipfip.v14i2.40253
|View full text |Cite
|
Sign up to set email alerts
|

Development of Instagram and YouTube Content Videos’ for Online Learning

Abstract: Instructional videos uploaded on Instagram and Youtube for online learning media teachers are facing a problem regarding the student's complicity in the learning process. To captivate the student's interest in the learning activity, the teacher needs to use innovative media. The study aims to develop an instructional video that is uploaded on Instagram and YouTube. The research used educational design research. The research procedure is 1) analysis of practical problems by the researcher; 2) development of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
5
0
3
Order By: Relevance
“…By using the media in the form of a specialization model application, school counselors can obtain a summary of the condition of each student based on academic data and psychological test results more efficiently. This is in line with research that has confirmed that the use of media in guidance and counseling is very effective in helping school counselors provide services to students (Dewanti & Sujarwo, 2021;Muti, 2021;Septyani et al, 2021). Accuracy in processing and summarizing learning outcomes and psychological test results will help school counselors provide more appropriate recommendations for student specialization so that students can determine careers more precisely.…”
Section: Introductionsupporting
confidence: 82%
“…By using the media in the form of a specialization model application, school counselors can obtain a summary of the condition of each student based on academic data and psychological test results more efficiently. This is in line with research that has confirmed that the use of media in guidance and counseling is very effective in helping school counselors provide services to students (Dewanti & Sujarwo, 2021;Muti, 2021;Septyani et al, 2021). Accuracy in processing and summarizing learning outcomes and psychological test results will help school counselors provide more appropriate recommendations for student specialization so that students can determine careers more precisely.…”
Section: Introductionsupporting
confidence: 82%
“…Selain itu guru juga mengunggah materi di platform diluar perencanaan seperti youtube atau whatsapp. Hal ini relevan dengan penelitian Kartimi, dkk., (2021); Dewanti & Sujarwo (2021); Baihaqi, (2021) bahwa kemudahan akses siswa terhadap sumber materi pembelajaran yang diunggah sekolah melalui berbagai platform, dan media sosial efektif membantu meningkatkan dan lebih memahamkan siswa pada suatu topik pelajaran. Disamping itu materi pembelajaran yang disediakan guru sudah dikembangkan agar siswa dapat memahami dan membangun konsep materi pembelajaran secara mandiri seperti video pembelajaran atau modul ajar.…”
Section: Pembahasanunclassified
“…This attracts attention because during the pandemic all learning management was carried out from home through the distance learning system with technology integration (Basilaia & Kvavadze, 2020;Nguyen, 2021;Wati & Yuniawatika, 2020;Yulia, 2020). The more advanced and developed forms of information technology are becoming very urgent to be applied in educational activities (Andewi & Pujiastuti, 2021;Dewanti & Sujarwo, 2021;Setyaningsih & Rahmawati, 2021). This is very important to prepare a generation that can adapt to future opposition.…”
Section: Introductionmentioning
confidence: 99%